A synoptic climatology of nocturnal rainfall events during May, June and July for northeast Kansas, 1950-2012 - Howard, Ian M. (Kansas State University, 2013)
Nighttime rainfall has long been thought of as an important component to the central Great Plains hydroclimate during the wettest three-month period known as the “late spring -early summer precipitation maximum.” Research has suggested that nocturnal rainfall in the region results from a phenomenon known as the nocturnal Great Plains Low-Level Jet (GPLLJ). The jet, which originates in the Gulf of Mexico, transports moisture into the Great plains during the nighttime hours and often provides fuel for nighttime convection. The climatological characteristics of nighttime rainfall, as well the configuration of the low-level winds and the mechanisms behind its formation during this three-month wet period, however; are not well understood. Using hourly rainfall data from Topeka, KS, the nighttime rainfall characteristics are examined Topeka, KS and other Kansas stations for a 63-year period from 1950-2012 for May-July. Additionally, using the NCEP/NCAR Reanalysis data, the structure and configuration of the southerly wind phenomenon was analyzed based on its horizontal and vertical characteristics for nighttime rainfall events in May, June and July. A subsequent analysis also analyzed the larger synoptic-scale environment in place for six half-month periods from May to July. The results indicate that nighttime rainfall is a major contributor to the overall moisture budget in the Great Plains, contributing close to 50% of the overall rainfall total for the three-month period. The percentage of nighttime rainfall increases from west-east across the state, as well as temporally from May to July. The southerly winds are at their strongest during May events, tends to reach its peak at 850 mb at 6z (0000LST) near south-central Oklahoma, and forms as the result of both synoptic and thermal mechanisms. The synoptic mechanisms in place that generate the a southerly wind component change by month, leading to incredible variation in terms of its characteristics during nighttime rainfall events.
Keywords: Nocturnal; Rainfall; Low-level jet; Great Plains; Synoptic climatology; Geography (0366)